2022
DOI: 10.1186/s12883-022-02556-x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Middle Eastern children with cancer: prevalence and risk factors

Abstract: Objective To determine the prevalence and to characterize the different types of strokes in children with cancer at the Children’s Cancer Center of Lebanon (CCCL), in addition to assess the factors and clinical findings leading to stroke in children. Methods We retrospectively reviewed the medical records and brain images (MRIs and CTs) of children admitted to the CCCL and diagnosed with cancer between years 2008 and 2017. Brain images were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In Sun et al, 12 a prothrombotic state was the most frequently identified risk factor in patients with CSVT, especially after asparaginase treatment. In the study by Zadeh et al, 15 half of the patients had coagulation abnormalities, with a history of asparaginase use in all the patients with CSVT. Other potential risk factors proposed were high initial white blood cell (WBC) count (median in ICH group of 374,925/mm 3 ), high peripheral blast cell count (median of 96%), and high initial lactate dehydrogenase level (median of 4140 mg/dL) 10 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In Sun et al, 12 a prothrombotic state was the most frequently identified risk factor in patients with CSVT, especially after asparaginase treatment. In the study by Zadeh et al, 15 half of the patients had coagulation abnormalities, with a history of asparaginase use in all the patients with CSVT. Other potential risk factors proposed were high initial white blood cell (WBC) count (median in ICH group of 374,925/mm 3 ), high peripheral blast cell count (median of 96%), and high initial lactate dehydrogenase level (median of 4140 mg/dL) 10 .…”
Section: Resultsmentioning
confidence: 98%
“…Three studies (Santoro et al, 13 Kuskonmaz et al, 11 and Intusoma et al 10 ) focused their research on stroke only in ALL patients. The other 3 studies included a mixed oncology population: Kyrnetskiy et al 14 (ALL, lymphoma, chronic myeloid leukemia, and brain tumors), Zadeh et al 15 (brain tumors, lung tumors, ALL, and lymphoma), and Noje et al 5 (ALL, lymphoma, and brain tumors). Campen et al 9 only analyzed patients with brain tumors, and Sun et al 12 did not report incidence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations